Pengaruh Strategi Pembelajaran Berdiferensiasi Terhadap Literasi dan Numerasi Siswa Sekolah Dasar - Ida Fitriyana; Juhana Juhana; Sri Dewi Nirmala (Jurnal Studi Guru dan Pembelajaran, 2024)
This research aims to explore the effect of differentiated learning on the literacy and numeracy of grade III elementary school students. The research method used was a quasi-experiment with a non-equivalent control group design. The research sample consisted of two classes with each class having the same student characteristics but different numbers. One class is the control group and the other class is the experimental group that receives differentiated learning. Data was collected through literacy and numeracy tests before and after the intervention. The results showed a significant increase in literacy and numeracy scores in the experimental group compared to the control group. Differentiated learning shows a positive impact in improving students' literacy and numeracy skills. These findings underline the importance of a learning approach that considers students' individual needs to improve their learning outcomes in the areas of literacy and numeracy, especially for grade III elementary scholl students.